The ref [videorecording (DVD)] - Leary, Denis; Davis, Judy, 1956-; Spacey, Kevin; Steinmiller, Robert J.; Johns, Glynis (Touchstone Home Entertainment, 2003)
An unfortunate cat burglar becomes trapped in a fate worse than jail when he takes a bickering couple and their annoying relatives hostage.